Hubungan Tingkat Asupan Protein Zat Gizi Mikro dan Frekuensi Diare dengan Status Gizi Balita di Desa Patas Kecamatan Gerokgak Kabupaten Buleleng - Dwijayanti, Yeni; Kencana, SKM.M.Pd, I Ketut; Widarti, DCN.M.Kes, I Gusti Agung Ari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
According to the Indonesia Nutrition Status Study 2021, 24.4% of toddlers are stunted, 17% are underweight, 7% are wasted, and 3.8% are overweight. The prevalence of diarrhea in Indonesia according to the 2018 Basic Health Research was 11.5% of diarrhea in children aged 1-4 years. According to the Indonesian Nutrition Status Study 2021, the proportion of children under five years of age with diarrhea in Bali Province is 11.2%. According to the 2020 Buleleng Health Profile, in the Gerokgak I Health Center working area there were 27.3% of diarrhea cases in toddlers. The purpose of this study was to determine the relationship between protein and micronutrient intake and the frequency of diarrhea with the nutritional status of toddlers in Patas Village. Type of observational research with cross-sectional design. This research was conducted in December 2022 in Patas Village. The research sample amounted to 84 samples. The sampling technique to be used is simple random sampling. The data analysis used is using the Pearson correlation test with α = 0.05. Based on statistical analysis test, there is a significant relationship between protein intake level and nutritional status of toddlers in Patas Village p=0.000. In addition, there is a meaningful relationship between the intake level of micronutrients calcium p=0.040 and phosphorus p=0.008 with the nutritional status of toddlers and there is meaningless relationship between micronutrients potassium p=0.322 with the nutritional status of toddlers. Then there is a relationship between the frequency of diarrhea and the nutritional status of toddlers in Patas Village p = 0.000 α (0.05). Keywords: Protein, Calcium, Potassium, Phosphorus, Diarrhea, Nutritional Status